Explicit Water Models Affect the Specific Solvation and Dynamics of Unfolded Peptides While the Conformational Behavior and Flexibility of Folded Peptides Remain Intact - Florová, Petra; Sklenovský, Petr; Banáš, Pavel; Otyepka, Michal (Journal of chemical theory and computation, 2010)
Conventional molecular dynamics simulations on 50 ns to 1 μs time scales were used to study the effects of explicit solvent models on the conformational behavior and solvation of two oligopeptide solutes: α-helical EK-peptide (14 amino acids) and a β-hairpin chignolin (10 amino acids). The widely used AMBER force fields (ff99, ff99SB, and ff03) were combined with four of the most commonly used explicit solvent models (TIP3P, TIP4P, TIP5P, and SPC/E). Significant differences in the specific solvation of chignolin among the studied water models were identified. Chignolin was highly solvated in TIP5P, whereas reduced specific solvation was found in the TIP4P, SPC/E, and TIP3P models for kinetic, thermodynamic, and both kinetic and thermodynamic reasons, respectively. The differences in specific solvation did not influence the dynamics of structured parts of the folded peptide. However, substantial differences between TIP5P and the other models were observed in the dynamics of unfolded chignolin, stability of salt bridges, and specific solvation of the backbone carbonyls of EK-peptide. Thus, we conclude that the choice of water model may affect the dynamics of flexible parts of proteins that are solvent-exposed. On the other hand, all water models should perform similarly for well-structured folded protein regions. The merits of the TIP3P model include its high and overestimated mobility, which accelerates simulation processes and thus effectively increases sampling.